2013
DOI: 10.1152/ajpendo.00251.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase plays a key role in palmitic acid-amplified inflammatory signaling triggered by lipopolysaccharide at low concentrations in macrophages

Abstract: Acid sphingomyelinase plays a key role in palmitic acid-amplified inflammatory signaling triggered by lipopolysaccharide at low concentrations in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
117
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(134 citation statements)
references
References 52 publications
16
117
0
1
Order By: Relevance
“…This hypothesis has been supported by the fact that there was a concomitant attenuation in the lysosomal sphingomyelinase activity in endothelial cells after cytokine stimulation (Marathe et al, 1998). In addition, inhibition of aSMase prevented the activation of Toll-like receptor 4 (TLR4) downstream of LPS stimulation (Jin et al, 2013). These results highlights the role of aSMase in inflammation and the possible beneficial use of its inhibitors in treating septic patients.…”
Section: Asmase In Pathophysiologymentioning
confidence: 82%
“…This hypothesis has been supported by the fact that there was a concomitant attenuation in the lysosomal sphingomyelinase activity in endothelial cells after cytokine stimulation (Marathe et al, 1998). In addition, inhibition of aSMase prevented the activation of Toll-like receptor 4 (TLR4) downstream of LPS stimulation (Jin et al, 2013). These results highlights the role of aSMase in inflammation and the possible beneficial use of its inhibitors in treating septic patients.…”
Section: Asmase In Pathophysiologymentioning
confidence: 82%
“…It is noteworthy that the stimulatory effect of PA on IL-6 expression in cardiac MIC ECs is cell type specific since PA failed to stimulate IL-6 expression in macrophages although it enhances the effect of LPS on IL-6 expression 32 . Furthermore, our time-course study as shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Active sphingolipids play an important role in regulating expression of pro-inflammatory genes 32, 34 . Therefore, we sought to elucidate the interactions between LPS and PA on sphingolipid metabolism in human cardiac MIC ECs and determine if sphingolipids are involved in IL-6 upregulation by LPS and PA.…”
Section: Discussionmentioning
confidence: 99%
“…CER has a wide range of biological functions in cellular signaling such as activating protein kinase C and c-Jun N-terminal kinase (JNK), induction of β-cell apoptosis and insulin resistance [61, 62]. CER increases reactive oxidizing species and activates the NF-κB pathway, which induces pro-inflammatory cytokines, diabetes and insulin resistance [63]. CER is synthesized from serine and palmitoyl-CoA or hydrolysis of SM by acid sphingomyelinase (ASM).…”
Section: Discussionmentioning
confidence: 99%